Prevalence of hepatitis and its correlation with serum ferritin and aminotransferase levels among thalassemia major patients in Indonesia - Pustika Amalia Wahidiyat; Felix Liauw; Nitish Basant Adnani; Siti Ayu Putriasih (Paediatrica Indonesiana, 2017)
Background Thalassemia major patients who undergo routine transfusion have an increased risk of acquiring transfusion-transmitted infections (TTI), including hepatitis B and C. These diseases have serious implications and may affect the serum ferritin and aminotransferase levels of thalassemia major patients.Objectives To identify the prevalence of hepatitis B and/or C infections among thalassemia major patients and to evaluate its correlation with serum ferritin and aminotransferase levels.Methods This was across-sectional study conducted at the Thalassemia Center of Dr. Cipto Mangunkusumo Hospital in Jakarta, Indonesia. The subjects were screened for hepatitis B and C infections, and their serum ferritin and aminotransferase levels were also measured.Results In total, 621 subjects were included in the study, among which 5 subjects tested positive for hepatitis B surface antigen (HBsAg) (0.8%), 111 subjects tested positive for anti-HCV (17.8%), and 5 subjects tested positive for both HBsAg and anti-HCV (0.8%). The subjects who tested positive for hepatitis B, hepatitis C, or both showed significantly higher values of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and serum ferritin compared to their negative counterparts. Moreover, serum ferritin showed a positive, moderate correlation with both AST and ALT.Conclusion This study shows a significant association between hepatitis and serum ferritin as well as aminotransferase levels. Early detection and early management of hepatitis B and C infections is warranted to minimize the occurrence of liver damage in thalassemia major patients.Â